Influence of postactivation potentiation on sprinting performance in professional rugby players - Bevan, H. R.; Cunningham, D. J.; Tooley, E. P; Owen, N. J; Cook, C. J.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2010)
After a bout of high-intensity exercise of short duration (preload stimulus), the muscle is in both a fatigued and potentiated (referred to as postactivation potentiation [PAP]) state. Consequently, subsequent muscle performance depends on the balance of these 2 factors. Although research has shown PAP to be an effective method of increasing power during both the squat jumps, little data exist on its effect on more functional activities such as sprinting. The present study aimed to determine the effect of PAP on sprint performance in professional rugby players. Sixteen professional male rugby players performed 5 10-m sprints (with a 5-m split): baseline, 4, 8, 12, and 16 minutes after the preload stimulus (1 set of 3 repetitions of the back squat at 91% 1 Repetition Maximum [RM]). There was no significant time effect over the duration of the study with regard to 5-m (p = 0.175) and 10-m sprint times (p = 0.401). However, when individual responses to PAP were taken into account, a significant improvement in sprint performance was observed over both 5 (Baseline: 1.09 ± 0.06s vs. Best time: 1.05 ± 0.05s, p = 0.002) and 10 m (Baseline: 1.83 ± 0.08s vs. Best time: 1.79 ± 0.08s, p = 0.003) compared with the baseline sprint. We conclude that sprinting performance is enhanced after a preload stimulus providing adequate and individualized recovery is given between the 2 activities, and this may have important implications for training speed.